Ionic Self-Assembled Wormlike Nanowires and Redox Induced Transition - Li, Qiuhong; Li, Aixiang (Asian Journal of Chemistry, 2011)
Wormlike nanowires have been prepared via the ionic self-assembly route from the cationic (ferrocenylmethyl)trimethylammonium iodide (FcMI) and the anionic sodium bis(2-ethyl-1- hexyl)sulfosuccinate (AOT). The formed FcM-AOT complexes have been proved to possess a composition of equal molar ratio. In response to redox stimuli, the nanowires can be changed into vesicles. The transformation of self-assembly aggregates induced by redox reactions were found to be brought out by drastic change in amphiphilicity of the supra-molecular complexes due to the oxidation ferrocenyl moiety.